The Implementation of Sports Through Cheerful Gymnastics Video in Improving The Learning Achievement of Students With Dyslexia: Learning With Students Without Obstacles - Ambarita, Uly Dame Ria; Sunardi, Sunardi (Dinasti Publisher, 2025)
Sports are activities that children enjoy in schools. Cheerful gymnastics, morning exercises with upbeat music, have movements adapted to songs favored by children. This study aimed to investigate the impact of daily morning sports on learning achievement at an elementary school in Surabaya. Sports activities were presented through videos to students with dyslexia integrated into a regular class. Dyslexia is characterized by difficulty in reading. The implementation spanned six months, with daily activities, observing the learning process, and collecting outcomes for each subject. The subjects were 4D elementary students at a private school in Surabaya. A qualitative descriptive method was used, detailing student conditions, the environment, and learning conditions. Achievement was measured by collecting and comparing data from each lesson to assess the impact of daily sports activities over six months. The results were significant, with fewer students requiring remedial tests/exams compared to other 4th graders.